Murs du son - Murmures. (Nice : Villa Arson Nice, 1995)
Armleder, John M ; Aubry, Michel ; Barry, Robert ; Fredrikson, Lars ; Gillick, Liam ; Joy, Jérôme ; Kongrosian, Richard ; Maillet, Eric ; Nannucci, Maurizio ; Oppenheim, Kristin ; Samakh, Erik ; Talec, Nathalie ; Broccolichi, Pascal ; LudovicLignon ; Orts, José Antonio ; Sordage, Isabelle
Speciale kast : CD
boek